The Synergy of Madrasah and Family Roles in Instilling Prayer Discipline Among Students - Saprudin; Najamuddin Petta Solong; Kusmawaty Matara; Yayah Nurmaliyah (Journal of Practice Learning and Educational Development, 2026)
This research aims to describe the role of madrasahs and families, as well as the synergy between the two, in instilling prayer discipline among students at Madrasah Tsanawiyah Negeri 1 Buol. The research employs a descriptive qualitative approach with data collection techniques thru observation, interviews, and documentation. The research informants consisted of the head of the madrasah, teachers, students, and parents. The data were analyzed using the Miles and Huberman model thru data reduction, data presentation, and conclusion drawing. The research results show that madrasahs play an important role in instilling prayer discipline thru the practice of congregational prayers, teacher supervision, religious activities, and the exemplary behavior provided by educators. Families play a role thru supervision, providing motivation, habituation of worship, and parental role modeling in the home environment. The synergy between madrasah and families is evident thru continuous communication, joint supervision of students' prayer practices, providing motivation, and consistent worship guidance carried out at home and in the madrasah. This study also found several obstacles in the discipline of prayer, such as the lack of supervision from some parents, the influence of social media, and the low awareness of some students in performing prayers without being reminded. Good synergy between the madrasa and the family has a positive influence on the formation of religious character and the discipline of students' prayers.